On "A framework for source code search using program patterns" - Devanbu, P. (IEEE transactions on software engineering, 1995)
The need to query and understand source code is an important practical problem for software engineers in large development projects. A paper by Paul and Prakash (1994) proposes a workable solution to this problem. However, there are several previously reported systems that can also address this problem. The relationship of their work to the body of existing work is the subject of the paper.